(3LRA ajg LhGH SDGd ef eGQOjf Yf HjJ TYQ eOM Hg GdfHi Udi Gddg Ydjg hSdes - (3TeS GdOjf eMeO Hf YHO Gddg Hf eMeO GdbjSi GdOeTbj GdeYQha HGHf fGUQ GdOjf,J (B842 (3g` s ((3eOQSI GdTjN GdESdGe CHj YeQ HSaM LHd bGSjhf s)
(3ChdgG (B:s
(3GdMeO ddg eXgQ GdMb hQGaYg CeG HYO aEf HYV ef CWgQ dSGfg eG WhJg WhjJg hGLfg LfGfg s
(3BNQgG (B:s
(3Whd GdReGf KfGA hai GdbjeI CLQ s
(3cJH HNW eged GdfbW fbdG Yf fSNI HNW GdeDdas
(3hYdi MGTjI fSNJfG gPg SeGY ef fGSNgG Ydi GdeDda hHBNQgG SeGY SfI (B837 (3Ydi GdeDda ef YOI YdeGA hefge GdfGSN faSg hTgO GdeDda Ydi gPG GdSeGY hELGRI HNWgs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B237s
Keywords: (3GdeLGejYs